Longitudinal Virological and Immunological Profile in a Case of Human Monkeypox Infection. (1st November 2022) - Zingaropoli, Maria Antonella; Parente, Alberico; Kertusha, Blerta; Campagna, Roberta; Tieghi, Tiziana; Garattini, Silvia; Marocco, Raffaella; Carraro, Anna; Tortellini, Eeva; Guardiani, Mariasilvia; Dominelli, Federica; Turriziani, Ombretta; et al.
Abstract: In a male with severe proctitis, monkeypox virus DNA was detected in skin lesions, blood, the nasopharynx, and the rectum, underlying generalized viral spreading. Rectal involvement was still found when skin lesions disappeared. At this early stage, an increase of cytotoxic and activated T cells was observed, while a reduction in CD56dimCD57+ NK cells compared with recovery time point was observed.